A1.35 Adiponectin isoform-mediated effects on P38 MAPK and AMPK pathways in rheumatoid arthritis synovial fibroblasts. (31st January 2014) - Khawaja, K; Frommer, KW; Bausch, M; Rehart, S; Müller-Ladner, U; Neumann, E
Abstract : Background: Adiponectin, a C1q/tumour necrosis factor homologue, was previously described to be secreted by adipocytes. Adiponectin levels were found to be increased in the synovial fluid of rheumatoid arthritis (RA) patients as compared to osteoarthritis patients, hence suggesting a role of adiponectin in the pathophysiology of the disease. RA synovial fibroblasts (SF) in addition to adipocytes are able to secrete adiponectin in the synovium in vivo . At present, four different adiponectin isoforms are known, namely globular, low-molecular-weight (LMW), middle-molecular-weight (MMW) and high-molecular-weight (HMW) adiponectin. Adiponectin acts by binding to its receptors AdipoR1, AdipoR2, and potentially PAQR3 and PAQR10. This leads to the activation of signalling cascades involving key signalling molecules like AMPK and p38 MAPK. The aim of the present study was to verify which signalling molecules are involved in the adiponectin-induced signalling in RASF and to analyse potential differences in the adiponectin isoform-mediated signalling. Methods: RASF were preincubated with serum-free medium for 30 min with or without signalling inhibitors. Stimulation of RASF was performed using the respective adiponectin isoforms: WT (wild type containing all isoforms), globular, LMW, and MMW/HMW-enriched adiponectin (each 10 µg/ml) for 10 min. Subsequently, phosphorylation of p38, AMPK, and FAK was analysed by Western blotting. Results: Phosphorylation of p38 was increased by all adiponectin isoforms, with the strongest induction by the MMW/HMW-enriched adiponectin (2-fold increase). Similarly, the phosphorylation of AMPK was increased in response to all adiponectin isoforms and the effect was again stronger with the MMW/HMW-enriched adiponectin (5-fold increase). On the contrary, although FAK was detectable in RASF, no alteration in FAK phosphorylation was observed in response to adiponectin isoform stimulation indicating that FAK does not play a role here. The adiponectin-mediated increase in phosphorylation of AMPK was further enhanced by the addition of the AMPK activator AICAR (e.g. 6-fold increase for WT adiponectin) and was reduced by the AMPK inhibitor compound C (e.g. 2-fold decrease for LMW adiponectin). Compound C caused an additional increase in the adiponectin isoform-induced phosphorylation of p38 (e.g. 2-fold increase for globular adiponectin), whereas pre-treatment with the p38 inhibitor SB203580 did not have any effect on the phosphorylation of AMPK. Conclusions: Adiponectin signalling in RASF is mediated via the p38 MAPK and AMPK pathway but not FAK, and the effect is adiponectin isoform-dependent. The data suggest that the p38 MAPK pathway is a compensatory pathway for the AMPK pathway but not vice versa . Funding: This work was supported by the German Research Foundation (DFG) (NE1174/8-1).